CURRENT TRENDS AND PROBLEMS OF DEVELOPMENT OF THE HOTEL MARKET OF KRASNOYARSK KRAI - Safronova, Tatyana Nikolaevna; Yabrova, Olga Alexandrovna; Kamoza, Tatyana Leontyevna; Evtukhova, Olga Mikhailovna (Nauka Krasnoi͡a︡rʹi͡a, 2019)
Development of the hotel markets of regions is connected with diversification of a tourist product, search of the new directions. One of major factors of development of regional tourism is change of economic, social, demographic conditions of development of regions. In work socio-economic indexes of Krasnoyarsk krai are presented, statistics of the market of hotel services and tourism for 2014–2018, their structure are analysed. Problems and current trends of development of the tourist and hotel markets of Krasnoyarsk krai are defined. The purpose – studying of the current state of the hotel market of Krasnoyarsk krai and trends of its development. Within work the following problems were solved: to define the current state of the tourist and hotel markets of Krasnoyarsk krai; to consider the main characteristics of the market and to define trends of its development. Object of a research were the hotel enterprises of Krasnoyarsk krai. Work is based on own researches, data of the state statistics. Research methods: statistical, general scientific methods of the analysis were used. Results: as a result of the proceeding political instability and decrease in real monetary income of the population the tourist market of Russia changed towards growth of internal tourism that led to growth of the hotel market. Development of the hotel market of Krasnoyarsk krai is connected with diversification of a tourist product, search of the new directions, reduction of average duration of trips, but increase in their frequency. Scope of results: results of a research can be useful to the regional authorities, specialists of the industry, the students studying in “Hotel business”.